Intelligent mobile private tutor finders application - Leong, Kam Ga (2022)
According to the official statistic from the Department of Statistics Malaysia (DOSM), there are 1899 tuition centers was established in Malaysia in 2010. The number of registered private tuition centers had increased to 3107 in Malaysia in 2013. T he dema nd for private tutoring services was elevated day by day due to the changes in the Malaysia examination and assessment system. In addition, it is a challenge to find a private tutor during this COVID19 pandemic because it has a high risk to meet with each of the tutors for choosing the most matched private tutor. However, there are only limited online platform s available in Malaysia while existing platform simple filtering criteria in the s only provide searching tutor function and only apply traditional se arching method s (SQL exact matching). Therefore, an intelligent mobile private tutor application is developed to help the tutor seeker in finding the ideal tutor that is highly matched their expectation at their fingertips. By putting aside the traditional searching method, this application applied similarity measures (Euclidean Distance, Manhattan Distance, Minkowski Distance, Jaccard Similarity Coefficient, and Cosine Similarity) to compare the similarity between one tutor with the ideal tutor s of the tutor seeker. The similarity percentage is considered as a metric for tutor seeker to choose the ideal tutor while not only relying on intuition. In addition, there are chat function s to tutor seeker s to , demo clas se s , and other functions provided have a formal channel to interact and communicate with tutor before com ing to the final decision of having a formal class. the After conducting the unit testing, API testing, usability testing, and User Acceptance Testing (UAT), the final product only appl ied the top three similarity measure methods in the search function. The final product of the project enables tutor seekers to search for their ideal tutor while also enabling tutors to expose themselves to more opportunities.